Novel III-V semiconductor epitaxy for optoelectronic devices through two-dimensional materials. (March 2021) - Zhao, Chao; Li, Zhaonan; Tang, Tianyi; Sun, Jiaqian; Zhan, Wenkang; Xu, Bo; Sun, Huajun; Jiang, Hui; Liu, Kong; Qu, Shengchun; Wang, Zhijie; Wang, Zhanguo
Abstract: III-V semiconductor materials are the basis of photonic devices due to their unique optical properties. There is an increasing demand for fabricating these devices on unconventional substrates for various applications, such as silicon photonic integrated circuits, flexible optoelectronic devices, and ultralow-profile photonics. However, the III-V semiconductor epitaxy often encounters problems from the lattice, thermal, and polarity mismatches with foreign substrates. In recent years, the epitaxial growth of defect-free group–III–V materials through two-dimensional materials has exploded as an attractive area of research. The nonconventional epitaxy way demonstrates potential advantages over conventional ones, including high quality and freedom of using diverse substrates, making them viable candidates for emerging applications. Herein, we offer a complete review of the recent achievements made in this field. We summarize the growth conditions and mechanisms involved in fabricating these structures through different two-dimensional materials. The unique optical properties of the epitaxy correlating with their growth conditions are discussed, along with their respective applications in optics and nanophotonics, including light-emitting diodes, photodetectors, and solar cells. Finally, we detail the remaining obstacles and challenges to exploit the potential for such practical applications fully.